Role perception and participation of the Lutheran Church women in Metro Manila - Juanillo, Emma Alunen B. 1931- (1977)
This study identified women's perception of their participation in Church activities. It looked into their role participation in three areas: Church, Community, and Family, and the Church as a context variable in accelerating their participation. One hundred eighty four (184) women from the 6 Metro Manila Lutheran parishes served as correspondents. A questionnaire consisting of 28 items which covered Worship/Witness, Christian Education, Christian Service, Citizenship activities, Welfare activities, and Cultural activities was administered to the respondents.
Appendices: leaves 93-121.
Mimeographed.
Thesis (M.A.)--University of the Philippines, Quezon City.
Vita.
Keywords: Lutheran Church in the Philippines; Women in church work -- Lutheran Church. -- Philippines -- Manila metropolitan area; Women christianity; Women in community development -- Philippines -- Manila metropolitan area